Sequence, evolution and ligand binding properties of mammalian Duffy antigen/receptor for chemokines - Tournamille, C.; Blancher, A.; Le van Kim, C.; Gane, P.; Apoil, P. A.; Nakamoto, W.; Cartron, J. P.; Colin, Y. (Springer, 2004)
The Duffy antigen/receptor for chemokine, DARC, acts as a widely expressed promiscuous chemokine receptor and as the erythrocyte receptor for Plasmodium vivax. To gain insight into the evolution and structure/function relations of DARC, we analyzed the binding of anti-human Fy monoclonal antibodies (mAbs) and human chemokines to red blood cells (RBCs) from 11 nonhuman primates and two nonprimate mammals, and we elucidated the structures of the DARC genes from gorilla, gibbon, baboon, marmoset, tamarin, night monkey and cattle. CXCL-8 and CCL-5 chemokine binding analysis indicated that the promiscuous binding profile characteristic of DARC is conserved across species. Among three mAbs that detected the Fy6 epitope by flow cytometric analysis of human and chimpanzee RBCs, only one reacted with night monkey and squirrel monkey. Only chimpanzee RBCs bound a significant amount of the anti-Fy3 mAb. Fy3 was also poorly detected on RBCs from gorilla, baboon and rhesus monkey, but not from new world monkeys. Alignment of DARC homologous sequences allowed us to construct a phylogenetic tree in which all branchings were in accordance with current knowledge of primate phylogeny. Although DARC was expected to be under strong internal and external selection pressure, in order to maintain chemokine binding and avoid Plasmodium vivax binding, respectively, our present study did not provide arguments in favor of a selection pressure on the extracellular domains involved in ligand specificity. The amino acid variability of DARC-like polypeptides was found to be well correlated with the hydrophylicity indexes, with the highest divergence on the amino-terminal extracellular domain. Analysis of the deduced amino acid sequences highlighted the conservation of some amino acid residues, which should prove to be critical for the structural and functional properties of DARC.
Keywords: Duffy blood group system; chemokine receptor; phylogenesis; DARC genes; nonhuman primates